Respuesta :

Answer:

[tex](x+4)^2 - 11 = 0\\[/tex]

a = 4

b = -11

Step-by-step explanation:

[tex]x^{2} +8x+5\\[/tex]

use the complete the square method:

[tex]x^{2} +8x+5=0\\x^{2} +8x = -5\\\\(x+4)^{2} = x^2 + 8x + 16\\\\x^2 + 8x + 16 = -5 + 16\\[/tex]

we completed the square of x^2 + 8x + ... which is x^2 + 8x + 16 using (x+4)^2

we added 16 to both sides because whatever you do to one side, you have to do to the other:

[tex]x^{2} +8x+16 = 11\\(x+4)^2 = 11\\(x+4)^2 - 11 =0[/tex]

ACCESS MORE